2012
DOI: 10.1016/j.ijscr.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic omentectomy for preoperative diagnosis of torsion of the greater omentum

Abstract: CT multi-planar reconstruction (MPR) imaging played a particularly important role in making a precise diagnosis. Laparoscopic approach could be useful in both diagnostic and therapeutic intervention. A successful laparoscopic omentectomy was performed in the present case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Treatment is resection of the affected omental segment, which could be performed laparoscopically [ 11 , 15 ]. However, some authors have reported successful non-operative treatment [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is resection of the affected omental segment, which could be performed laparoscopically [ 11 , 15 ]. However, some authors have reported successful non-operative treatment [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As diaphragmatic hernia requires surgical repair, recent reports demonstrated that laparoscopic simple closure is effective [ 7 ]. The laparoscopic approach for an acute abdomen is less invasive and promotes a faster recovery in patients with stable vital signs and no previous medical history of surgery [ 18 ]. Timely and accurate diagnosis of this disease is important because these patients have severe liver dysfunction; therefore, colon necrosis leads to poor prognosis even after curative treatment.…”
Section: Case Presentationmentioning
confidence: 99%
“…De realizarse, se recomienda apendicectomía en el mismo tiempo quirúrgico para evitar confusiones diagnósticas a futuro, incluyendo una posible recurrencia de torsión omental. 6,8,11 En el caso reportado, se optó por la resolución quirúrgica debido al tiempo de evolución, recurrencia, valoraciones previas de distintos servicios y manifestaciones de respuesta inflamatoria sistémica.…”
Section: Discussionunclassified